La agonía del Imperio Romano de Occidente - Fernández, Gonzalo (Gerión. Revista de Historia Antigua, 2005)
This article deals with some problems concerning roman history in years 472 – 476 A.D. The main sources are John of Antioch, Priscus, Procopius of Caesarea and Malchus.